Design of the Gear Generating Instrument on the type of Duplicate Planetary Transmission - Ye Youdong; Liu Lihong (Jixie chuandong)
The structure and function of the existing gear generating instrument are analyzed,its drawbacks and deficiencies of the structure and using are pointed out.The traditional structure mode of gear generating instrument is abandoned,and a new type of duplicate planetary transmission of involute gear generating instrument is designed,and then the structure,parameters,principle and characteristics are introduced.The duplicate planetary transmission of involute gear generating instrument is more convenient and quicker for operating by contrast of using the old and new gear generating instrument,and it can completely replace the existing gear generating instrument.